Assessment of information quality in the largest Danish Facebook group on atopic diseases: a mixed bag of help and harm - Høj, Simon; Thomsen, Simon Francis; Meteran, Hanieh; Sigsgaard, Torben; Meteran, Howraman (Frontiers in Allergy, 2025)
BackgroundPatient education is an important part of the management of atopic diseases such as allergic rhinitis, atopic dermatitis, and asthma. Given the increasing reliance on social media platforms such as Facebook for health-related discourse, there are concerns about the accuracy and quality of the shared information.AimThe aim of this study was to categorize and assess the quality of the information shared within the largest Danish Facebook group focusing on atopic diseases.MethodA total of 652 posts and 7,515 comments were scrutinized, classifying each as useful, misleading, or neutral.ResultsThe analysis predominantly identified discussions around asthma (40%), allergic rhinitis (21%), and eczema (5%), with the majority of queries posed by women and related to symptoms and medications. The results indicated that 11% of comments were deemed useful, whereas 12% were categorized as misleading, with the bulk of comments being neutral. Concerningly, 52% of the comments promoting behavioral change were found to be misleading.ConclusionAlthough the Facebook group serves as a hub for peer support, its utility as a reliable educational resource is compromised. Overall, 12% of the comments were classified as misleading, while more than half of the advice encouraging behavioral change was misleading.